2021
DOI: 10.3389/fncel.2021.768364
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Inhibits Microglial Activation via miR-106b/Pi3k/Akt Axis

Abstract: Propofol is an established intravenous anesthetic agent with potential neuroprotective effects. In this study, we investigated the roles and the underlying mechanisms of propofol in inhibiting the pro-inflammatory responses of microglia. Propofol significantly reduced the messenger RNA (mRNA) levels of Tnf, Nos2, and NF-κB pathway related genes Ticam1, Myd88, Irf3, and Nfkb1 in lipopolysaccharide (LPS)-treated primary microglia. After screening the miRNA profiles in microglia under LPS and propofol treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In a recent in vitro model, miR-124 overexpression with a concomitant decrease of its target (VAMP3) expression led to a decrease of inflammatory factors associated with microglial activation post-surgery ( Chen et al, 2019b ). Other microRNA types and their targets, including miR-155/SOCS1 ( Zheng et al, 2018 ), and miR-106b/Dusp9 ( Liu et al, 2021 ), were suggested to regulate microglial function in LPS-activated microglia treated by anesthetic agents.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…In a recent in vitro model, miR-124 overexpression with a concomitant decrease of its target (VAMP3) expression led to a decrease of inflammatory factors associated with microglial activation post-surgery ( Chen et al, 2019b ). Other microRNA types and their targets, including miR-155/SOCS1 ( Zheng et al, 2018 ), and miR-106b/Dusp9 ( Liu et al, 2021 ), were suggested to regulate microglial function in LPS-activated microglia treated by anesthetic agents.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…However, the top-ranking predicted miRNAs were hsa-miR-106a-5p and hsa-miR-106b-5p. miR-106 is associated with microglial activation and neuroinflammatory diseases ( Liu et al, 2021 ). Given the complexity of its regulatory network, miR-106 may represent an essential target for the regulation of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has confirmed that propofol targets NF-kB and its upstream signaling pathways to inhibit microglial activation in vivo and in vitro (80,(108)(109)(110). Microglial activation in the spinal cord induced by peripheral inflammation can be reversed by propofol via inhibition of the MAPK ERK1/2/NF-kB pathway (80).…”
Section: Intravenous Anesthetics 411 Propofolmentioning
confidence: 99%
“…Microglial activation in the spinal cord induced by peripheral inflammation can be reversed by propofol via inhibition of the MAPK ERK1/2/NF-kB pathway (80). In the LPS-induced cell model, the release of pro-inflammatory cytokines and the genes TICAM1, IRF3, and NFKB1 involved in NF-kB pathway are downregulated by propofol (108,109). TLR4 and its adaptor protein MyD88, key upstream inflammatory mediators that activate NF-kB, are also downregulated by propofol, thus inhibiting the microglial activation induced by LPS (110,111).…”
Section: Intravenous Anesthetics 411 Propofolmentioning
confidence: 99%
See 1 more Smart Citation